A UNIQUE LITERARY WORK OF THE EAST (International journal of artificial intelligence, 2025)
Years, decades, centuries pass, but the interest of readers, philologists, and orientalist historians in the outstanding literary work called “A Thousand and One Nights” does not fade. These tales express with amazing perfection the harmony and extraordinary power of the colorful, “patterned” fantasy of the peoples of the East: Arabs, Persians, Hindus, and other peoples.The article examines scientific ideas about the creation of “A Thousand and One Nights” — a unique work of oriental literature. Scientific hypotheses of Russian, European, and Uzbek orientalists about the origin of this masterpiece are presented as a subject of discussion. At the same time, information about the composition of the work is provided.